2018
DOI: 10.1016/j.kontakt.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of falling in patients with neurological diseases

Abstract: A B S T R A C TPurpose: The aim of the study was to perform a fall risk screening and to identify the risk factors for falling in hospitalized patients with neurological disease aged up to and over 65 years. Design: A quantitative prospective cross-sectional study. Methods: The sample consisted of 103 patients who were hospitalized in the neurological unit. Empirical data was recorded in the research protocol, which included selected fall risk factors and the Morse Fall Scale (MFS). Results: Significant fall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
3
3
0
Order By: Relevance
“…As complications of the nutrition, vomiting, inflammation around PEG, as well as inflammation around TSK, which might have been caused by vomiting, were reported. The possibility of the same complications is also reported by Miertová et al (2015). Other complications in patients of the sample were inflammation of the oral cavity (stomatitis) and inflammation of the conjunctiva of the eye (conjunctivitis) - Table 2.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As complications of the nutrition, vomiting, inflammation around PEG, as well as inflammation around TSK, which might have been caused by vomiting, were reported. The possibility of the same complications is also reported by Miertová et al (2015). Other complications in patients of the sample were inflammation of the oral cavity (stomatitis) and inflammation of the conjunctiva of the eye (conjunctivitis) - Table 2.…”
Section: Discussionsupporting
confidence: 67%
“…There are problems of constipation and diarrhea when emptying the colon. These problems may alternate (Miertová et al, 2015). Complications with emptying were also observed in our sample ( Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…This is also in line with the results of a secondary study analysis in which an abnormal gait is identified using Morse Fall Scale (MFS) the result is 51% (n = 224) of falls (Guillaume et al, 2016). There is also a study involving 103 patients, patients with a high risk of falling, there are predictors signification of the incidence of falls: gait and balance disorders (Miertová et al, 2018). However, another study related to risk of falls inpatients involving 1,487 patients found that the results of the study using the Morse Fall Scale (MFS) showed that patients who had previous walking disorders experienced falls as much as 10% of patients who fell with p < 0.0001, which is of significant significance.…”
Section: High-risk Intrinsic Factorsupporting
confidence: 75%
“…However, there is another study that has been carried out, namely a cohort study involving 831 patients in several surgical and medical clinics in Brazil, the results of which were found in the Morse Fall Scale (MFS) study that the number of patients who did not have a history of falls was 151 (53, 2%) patients (Pasa et al, 2017. The results of this literature review also show that the patient's gait is one of the intrinsic factors that enter into a high-risk intrinsic factor. Triggers of gait factors in the incidence of falls in patients such as muscle weakness, lower extremity weakness, balance disorders and walking problems besides utu are certain drugs that can cause walking disorders and increase the risk of falling (Guillaume et al, 2016;Lee et al, 2020;Miertová et al, 2018;Noh et al, 2021;Urbanetto et al, 2017). Therefore, assistance is needed when the patient walks or even the patient can use a walking aid that is adapted to the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…The tool was suitable even for those purposes and is very useful in practice [ 37 ]. The tool was also supported by Miertova et al, who recommend it for use in emergency care and for patients with neurological diseases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%